Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1101/829614
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cortical cell stiffness is independent of substrate mechanics

Abstract: Cortical stiffness is an important cellular property that changes during migration, adhesion, and growth. Previous atomic force microscopy (AFM) indentation measurements of cells cultured on deformable substrates suggested that cells adapt their stiffness to that of their surroundings. Here we show that the force applied by AFM onto cells results in a significant deformation of the underlying substrate if it is softer than the cells. This 'soft substrate effect' leads to an underestimation of a cell's elastic … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 55 publications
3
17
0
Order By: Relevance
“…Last but not least, a recent study has reported that AFM indentation can push cells into soft substrates. 40 Consequently, the resultant moduli are influenced by the properties of the soft components under the cells, and thus are significantly lower than the moduli of the cells themselves. This is likely happening in tissues, where cells sit in soft extracellular matrices.…”
Section: Discussionmentioning
confidence: 99%
“…Last but not least, a recent study has reported that AFM indentation can push cells into soft substrates. 40 Consequently, the resultant moduli are influenced by the properties of the soft components under the cells, and thus are significantly lower than the moduli of the cells themselves. This is likely happening in tissues, where cells sit in soft extracellular matrices.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that traction forces transmitted to the cortex might dissipate quickly so that overall cortical tension would not scale with local traction forces 22 . If cortical and membrane tension are coupled, changes in membrane tension on the different hydrogels would happen only locally 29 near focal adhesions and cannot be seen when probed further away.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, actomyosin-based traction forces scale with substrate stiffnesses for both neurons and fibroblasts 22 . Also in our culture conditions, cellular traction forces significantly increased on stiffer substrates in both cell types within the investigated stiffness range (Fig.…”
Section: Tether Forces Are Independent Of Hydrogel Stiffness But Pfs On Glass Depend On Cell Typementioning
confidence: 97%
See 1 more Smart Citation
“…Here, it should be noted that AFM, in general, is a surface characterization technique. However, on materials like hydrogels, indentations with a spherical probe will result in deformation many microns deep into the hydrogel 60 . Thus, the resulting mechanical response will be that of a combination of the overlying hydrogel, the cells or organoids themselves, and their surrounding matrix 59 .…”
Section: Applications Of the Methodsmentioning
confidence: 99%